Mapping the vulnerability of banana production landscapes in Uganda to banana bunchy top disease - Ocimati, Walter; Ogwal, Geofrey; Tazuba, Anthony Fredrick; Kubiriba, Jerome; Tugume, Joab; Erima, Rockefeller; Okurut, Wilson; Mahuku, George; Kutunga, David; Blomme, Guy (Frontiers in Agronomy, 2024)
IntroductionBanana bunchy top disease (BBTD) caused by banana bunchy top virus (BBTV) poses a significant threat to Uganda’s food and income security.MethodsTo map BBTD spread and inform its management, a delimiting survey was undertaken covering the high-risk zones bordering the Democratic Republic of Congo (DR Congo) in the west, Rwanda and Tanzania in the south, and South Sudan in the north. BBTD is endemic in the DR Congo and present in Tanzania and Rwanda. The survey and environmental data were then used to map the vulnerability of Uganda’s banana landscapes.Results and discussionBBTD was only confirmed on 9% of sampled farms in north- and midwestern Uganda, with yield losses of 75% to 100%. Farmers observed BBTD over a 0.5–4.4-year period, suggesting a delayed detection. Suckers were the predominate planting materials used, increasing the risk of disease spread. Landscape suitability for BBTD was influenced by precipitation of the driest month, banana presence in 2016, land surface temperature difference (LSTD), the interaction between wind speed and LSTD, isothermality, wind speed, and the normalized difference vegetation index. These variables affect either or both the virus and aphid vector populations. Altitude did not influence the model, possibly due to disease introduction at mid to high altitudes through infected planting materials. The low-lying zones (around River Nile and Lakes Albert, Edward, and Victoria) are highly vulnerable. BBTD risk was low in northeastern Uganda with low banana production. The prediction map shows some suitable landscapes in the southwest that can expose this major banana production zone to BBTD, necessitating proactive measures.